The Role Of Product Market Competition On Corporate Social Responsibility (Csr) : Evidence In Malaysia - Chung, Min Hui (Universiti Malaysia Sarawak (UNIMAS), 2016)
The purpose of this research study is to investigate the influence of product market competition and other characteristics of finn on corporate social responsibility in Malaysia. Characteristics of firm such as finn age, finn profitability and firm leverage. The theories such as stakeholder theory, institutional theory and instrumental theory used in this research study also need to be examined to assure the accuracy. The sample of this study includes 7 industries such as construction, consumer, plantation, property, industrial property, technology and trading and service industry. The regression model in chapter 3 in this research study is panel regression model which the appropriateness of this model confirmed by the breusch-pagan LM test. According to panel regression model, the main independent variable such as product market competition and control variables such firm age, firm profitability and finn leverage have significant and positive relationship on corporate social responsibility.